Electroacupuncture Promotes Central Nervous System-Dependent Release of Mesenchymal Stem Cells. (25th April 2017) - Salazar, Tatiana E.; Richardson, Matthew R.; Beli, Eleni; Ripsch, Matthew S.; George, John; Kim, Youngsook; Duan, Yaqian; Moldovan, Leni; Yan, Yuanqing; Bhatwadekar, Ashay; Jadhav, Vaishnavi; Smith, Jared A.; et al.
Abstract : Electroacupuncture (EA) performed in rats and humans using limb acupuncture sites, LI-4 and LI-11, and GV-14 and GV-20 (humans) and Bai-hui (rats) increased functional connectivity between the anterior hypothalamus and the amygdala and mobilized mesenchymal stem cells (MSCs) into the systemic circulation. In human subjects, the source of the MSC was found to be primarily adipose tissue, whereas in rodents the tissue sources were considered more heterogeneous. Pharmacological disinhibition of rat hypothalamus enhanced sympathetic nervous system (SNS) activation and similarly resulted in a release of MSC into the circulation. EA-mediated SNS activation was further supported by browning of white adipose tissue in rats. EA treatment of rats undergoing partial rupture of the Achilles tendon resulted in reduced mechanical hyperalgesia, increased serum interleukin-10 levels and tendon remodeling, effects blocked in propranolol-treated rodents. To distinguish the afferent role of the peripheral nervous system, phosphoinositide-interacting regulator of transient receptor potential channels (Pirt)-GCaMP3 (genetically encoded calcium sensor) mice were treated with EA acupuncture points, ST-36 and LIV-3, and GV-14 and Bai-hui and resulted in a rapid activation of primary sensory neurons. EA activated sensory ganglia and SNS centers to mediate the release of MSC that can enhance tissue repair, increase anti-inflammatory cytokine production and provide pronounced analgesic relief.